Loch Ness Monsters as cryptid (presently unknown) sea turtles - Bauer, Henry (Journal of Scientific Exploration, 2020)
The most popular attribution of identity for Loch Ness Monsters is a relationship with the extinct plesiosaurs, but this is difficult to square with the rarity of surface sightings let alone occasional sightings on land. On the other hand, everything described for Loch Ness Monsters is known among the many species of living as well as thought-to-be extinct turtles: air-breathing but spending very long periods in deep water; ventures onto land; very fast movement in water; ability to be active in very cold water; relatively long necks. It is suggested that Loch Ness Monsters, Nessies, are a yet-to be properly discovered and described variety of large sea turtle that is most likely also still extant in some specific niches in the oceans.